Possibility of using a mouse SCID as a model animal to variola virus for evaluating anti-smallpox drug efficacy - K. A. Titova; Al. A. Sergeev; A. S. Kabanov; L. E. Bulychev; Ar. A. Sergeev; D. O. Galahova; A. S. Zamedyanskaya; L. N. Shishkina; O. S. Taranov; V. V. Omigov; E. L. Zavjalov; A. P. Agafonov; et al. (Вавиловский журнал генетики и селекции)
At present, there is no animal model for smallpox that reflects the weakened immune system in people and can therefore help assess the prophylactic (highly preventive) efficiency of antiviral drugs. To fill in the gap, we have explored the possibility of using outbred immunodeficient SCID mice as a model animal for smallpox with the aid of virological, histological and electron microscopic and statistical methods. There was no clinical evidence of disease by intranasal infection of mice at a dose of 5.2 log10 PFU (plaque forming units). At the same time, the 50 % infective dose (ID50) of VARV estimated for animals by registering the presence of the virus in their lungs after 4 days post i.n. infection was 3.5 log10 PFU and was relatively similar to that in humans, theoretically determined by identification of the clinical picture of the disease. Virus replication was detected only in the respiratory organs of mice challenged i.n. with VARV at a dose of 5.2 log10 PFU (50 ID50). The values for its concentrations in the lungs and nose resembled those for affected people and well-known animal models (Macaca cynomolgus and ICR mice), respiratorily infected with VARV at similar doses. The existing model animals were not significantly different from SCID mice in the duration of viral presence in the lungs. Moreover, in SCID mice, as in humans and other animal models, similar pathomor- phological changes of inflammatory necrotic nature in the respiratory organs have been reported. Using SCID mice in assessing the prophylactic efficacy of the antiviral drugs NIOCH-14 and ST-246 demonstrated the adequacy of the results obtained to those described in the literature. This opens up the prospect of using SCID mice as an animal model for smallpox to develop antiviral drugs intended for people with severe immunosuppressive states.